Neural Information Processing 16th International Conference, ICONIP 2009, Bangkok, Thailand, December 1-5, 2009, Proceedings, Part II - Leung, Chi Sing.; Lee, Minho; Chan, Jonathan H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The two volumes LNCS 5863 and 5864 constitute the proceedings of the 16th International Conference on Neural Information Processing, ICONIP 2009, held in Bangkok, Thailand, in December 2009. The 145 regular session papers and 53 special session papers presented were carefully reviewed and selected from 466 submissions. The papers are structured in topical sections on cognitive science and computational neuroscience, neurodynamics, mathematical modeling and analysis, kernel and related methods, learning algorithms, pattern analysis, face analysis and processing, image processing, financial applications, computer vision, control and robotics, evolutionary computation, other emerging computational methods, signal, data and text processing, artificial spiking neural systems: nonlinear dynamics and engineering applications, towards brain-inspired systems, computational advances in bioinformatics, data mining for cybersecurity, evolutionary neural networks: theory and practice, hybrid and adaptive systems for computer vision and robot control, intelligent data mining, neural networks for data mining, and SOM and related subjects and its applications.
Computer Vision -- Control and Robotics -- Evolutionary Computation -- Other Emerging Computational Methods -- Signal, Data and Text Processing -- Artificial Spiking Neural Systems: Nonlinear Dynamics and Engineering Applications -- Towards Brain-Inspired Systems -- Computational Advances in Bioinformatics -- Data Mining for Cybersecurity -- Evolutionary Neural Networks: Theory and Practice -- Hybrid and Adaptive Systems for Computer Vision and Robot Control -- Intelligent Data Mining -- Neural Networks for Data Mining -- SOM and Related Subjects and Its Applications.
Keywords: Computer science; Computers; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computer simulation; Pattern recognition; Computer Science; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Simulation and Modeling; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Electronic books